Efektivitas Pelatihan Patient Safety; Komunikasi S-BAR pada Perawat dalam Menurunkan Kesalahan Pemberian Obat Injeksi di Rumah Sakit PKU Muhammadiyah Yogyakarta Unit II - Fatma Siti Fatimah; Elsye Maria Rosa (Alma Ata University Press, 2016)
Health services provided in the hospital are likely to cause patient safety incidents which are adverse patient. The most incidents occurred in Indonesia are errors drug administration. Incidents can be prevented, one of them by training nurses on patient safety with S-BAR approach communications. The study aimed to determine the effectiveness of patient safety training; S-BAR communication in reducing injection drug administration errors in PKU Muhammadiyah Hospital in Yogyakarta Unit II. The type of research pre-experiment with the design of one group pretest-posttest design. Respondents were taken by purposive sampling technique, which total of 32 nurses who fulﬁlled the inclusion criteria. This study used the observation sheet instruments of 10 true principle of injection drug delivery. Analyzed by Wilcoxon test. After the training of patient safety: the SBAR communication given to nurses, there were signiﬁ cant differences in injection drug administration errors based on the principle really patient, route, medicine, time, assessment, information and evaluation (p<0.05), but no signiﬁ cant differences in principle correct dose, expired and documentation (p> 0.05). Conclusions and suggestions: patient safety training; SBAR communication on nurses wasc reduced injection drug administration errors effectively in PKU Muhammadiyah Hospital Unit II Yogyakarta based on the principle of right of patients, service, medicine, time, assessment, information and evaluation. Suggested Hospital to provide periodic training to all health workers, considering the creation of a patient safety culture is the responsibility of all parties in the Hospital. Thus increase the productivity of health workers as well as the creation of a patient safety culture.